Diseño y construcción de un prototipo de máquina despicadora de pollos. - Palacios Jimenez, Pio Oswaldo (2022)
This project is about the design and the construction of a semi-automatic machine for debeaking chicken, as an alternative to make easier the activity of debeaking, especially for the workers on the local poultry farms. It first focused on finding information about present debeaking machines, recognizing their main parts, and the way they work. Secondly, all these parts and mechanisms were considered for the design proposal of the machine, which ended up having the cutting and the cautery mechanisms separately. For the cutting mechanism design, the size of the chicken beaks was analyzed previously, making field measurements, as well as tests to know its internal structure, proposing in this way a guillotine-type mechanism. The design of this guillotine was also made, considering the available local materials and parts, as well as its future maintenance. On the other hand, its main parts went through calculations using the theory of fatigue, due to having moving parts. About the construction of the cauterization mechanism, the same was carried out experimentally, determining an effective temperature to cauterize the chicken peaks, and also using materials that were locally available. The electrical control of the machine was developed with the use of magnetic contactors and a limit switch, which represented an easy and reliable alternative. Finally, the machine was tested, using fifty beaks from dead adult chickens, and ten live ones, acquired from a local chicken slaughterhouse, having very good results in terms of its cutting precision and the uniformity in cauterization. Key words: chicken debeaking, machine, beaks, chickens, poultry farms